The best of horizon genetics - Dugan, david; Cadbury, Deborah; Peck, Danielle; Smith, Jacqueline; BBC Learning ([S.l.] : BBC Learning)
This video overview about genetics, genetics engineering and cloning
episode 1. Brave New Baby? David Dugan and Oliver Morse - episode 2. Dawn of the clone age Deborah Cadbury - episode 3. Designer babies Danielle peck - episode 4. Cloning the first human Jacqueline Smith
Presenter: Steve jones
Keywords: Genetics -- Juvenile literature; Cloning; Human genetics